TEACHER IN ONESELF AND WITH ONESELF - Kozhevnikova, Margarita (Acta Paedagogica Vilnensia, 2013)
The article is intended primarily to consider “teacher’s self-consciousness” as a category of philosophy of education and to identify the range of problems that can be associated with it. The author examines the approaches to the problem presented in the modern Western and traditional Eastern (Buddhist) educational thought regarding the description of the phenomenon of teacher’s self-consciousness; the processes of its functioning; the problems connected with it, such as gaps in teacher’s identity and other; opportunities for its cultivating, etc. The author’s idea is that teacher’s self-awareness can be revealed and developed through a special teachers’ workshop of philosophical self-determination; so, the conclusion of the article includes some remarks based on reviewed traditions, which should be taken into consideration in terms of such course.
Keywords: philosophy of education; teachers’ self-consciousness; reflective teaching; Buddhism